Effects of diet restriction on life history in a sexually cannibalistic spider. (16th December 2015) - Yip, Eric C.; Lubin, Yael
Abstract : Diet restriction increases longevity while reducing fecundity in a broad range of organisms. However, there are exceptions to this rule, and the causes of these exceptions remain unclear. One hypothesis is that short‐lived, semelparous organisms gain no benefit from increased longevity regardless of nutritional resources. Another hypothesis is that organisms may alter their behaviour to compensate for nutrient deficiencies. We examined these hypotheses in the colonial orb‐weaving spider Cyrtophora citricola . Sexual cannibalism is frequent in this species so that females are long lived and interoparous while males are semelparous. Because of these differing sexual strategies, we predicted that the common pattern of increased longevity under diet restriction would hold for females but not for males. We also investigated in a semi‐natural setting whether spiders could compensate for diet restriction by altering their feeding behaviour. Diet‐restricted females produced fewer offspring but lived longer than well‐fed females, while diet had no effect on male longevity. Despite being semelparous, virgin males were quite long‐lived, suggesting that potential lifespan is relatively unimportant in determining the effects of diet restriction. Contrary to our predictions, females were unable to compensate for their restricted diet by altering their foraging behaviour. Instead, semi‐natural conditions increased the differences between spiders on high and low diets, suggesting that the effects of diet restriction can be pervasive under natural conditions.